Dinamika Pengembangan Kurikulum Pendidikan Agama Islam di Madrasah: Studi Perbandingan Penerapan Subject Centered Curriculum di Kabupaten Bekasi - Asep Nursalim; Nico Verdianto (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
In the context of the dynamics of curriculum development in Indonesia, the PAI curriculum still faces various problems in its development. This is due to differences in school ownership status, school environment, and available human resources. This study aims to analyze the problem of the application of development, construction, and supporting factors and inhibitors of the PAI curriculum in MTs An-Najah Bekasi and MTs Al-Hidayah Bekasi. This study uses field research with multi-site studies at two different institutions in Bekasi Regency. The results showed that the curriculum construction of the two madrassas focused on Subject Centered Design, which focused on subjects. This research is still limited to the implementation of the PAI curriculum in the two madrassas, so it is hoped that there are still many other studies with different locations so that it can be used as a source of research. Whereas the most dominant determinants are human resources and infrastructure. Comparison of curriculum construction models in the two madrassas lies in the essence and depth of the material. From the data of the two madrassas, the collaborative curriculum becomes a curriculum redesign choice that is considered ideal and can be applied.